IMPLEMENTASI PROGRAM KOTA SERANG SEHAT DALAM MEWUJUDKAN PEMBANGUNAN KESEHATAN BERKELANJUTAN DI KOTA SERANG - Yeni Widyastuti; Arenawati Arenawati; Listyaningsih Listyaningsih (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2020)
Kota Sehat (Healthy City) as one program that continues to be developed with public policies and creates physical and social environments that enable people to support one another in carrying out all life functions and achieving their full potential (Healthy Toronto 2000 Subcommittee, 1988). The implementation of Kota Serang Sehat which began in 2013 until now has not run optimally as a whole, especially related to the implementation of 9 (Nine) District / City Health Arrangements and the role and function of the Serang Sehat City Forum (FKSS) and the Serang Sehat District Communication Forum (FKKSS) ). However, several key indicators show improvements in achieving the Sustainable Development Goals (SDGs) targets. Infant Mortality Rate (IMR) decreased from 31 cases in 2014 to 21 cases in 2018 (source: Dinas Kesehatan Kota Serang, 2019). On the other hand, there has been a very large increase in the number of deaths in 2017 and 2018, where in 2017 there were 85 deaths, and in 2018 there were 81 cases for toddlers aged 1 year to 4 years 11 months. The next main indicator is the Maternal Mortality Rate (MMR) where in 2014 there had 6 cases increased sharply in 2018 to 24 cases, or increased 400 percent or quadrupled (Source Dinas Kesehatan Kota Serang, 2019). In connection with the City Spatial Planning General Plan (RUTRK) in general, it has supported the implementation of Serang Sehat City by structuring slums, developing the supply and access to clean water and in terms of managing and overcoming the waste problem. For general indicators related to the support of the Regional Government for the City of Serang Sehat, to increase community participation and in terms of budgeting already support the APBD, but each work program embedded in the activities of each OPD has not been coordinated or the emergence of sectoral egos or not integrated yet. Then the support from CSR is also not optimal. Research recommendations are optimizing the Minimum Service Standards Coverage (SPM) in Health and involving all sectors, especially services related to family health for mothers and children (infants and toddlers) so as to reduce the maternal mortality rate (MMR) and infant and toddler mortality rates (MMR) AKB and Akaba) towards meeting Sustainable Development Goals (SDGs) standards. Next is the optimization of the role of each element in the Serang Sehat City Forum, full support from the local government and the maximum CSR functionKeywords: Kota Serang Sehat; Sustainable Development Goals (SDGs)